2023
DOI: 10.1111/1471-0528.17655
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum azithromycin to prevent maternal and neonatal sepsis and deaths: A systematic review with meta‐analysis

Ilari Kuitunen,
Maiju Kekki,
Marjo Renko

Abstract: ObjectivesA systematic review with met‐analysis was performed to summarise the evidence on the effect of intrapartum azithromycin on maternal and neonatal infections and deaths.Search strategyPubMed, Scopus and Web of Science databases were searched in March 2023.Selection criteriaRandomised controlled trials comparing intrapartum single‐dose of azithromycin with placebo.Data collection and analysisMaternal infections, maternal mortality, neonatal sepsis, neonatal mortality. We used the random‐effects Mantel–H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The azithromycin group had a lower incidence of maternal sepsis than the placebo group did (RR = 0.65, CI (0.55-0.77)), but there was no statistically signi cant difference between the two groups in terms of maternal all-cause mortality, neonatal sepsis or all-cause mortality. Two recent systematic reviews [19,20] showed that the addition of a single dose of azithromycin at the time of delivery was associated with a lower risk of maternal sepsis but was not associated with maternal mortality, neonatal mortality, neonatal sepsis or suspected neonatal sepsis. The ndings of our systematic review are consistent with those of Tita et al's [13] research and two previous systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…The azithromycin group had a lower incidence of maternal sepsis than the placebo group did (RR = 0.65, CI (0.55-0.77)), but there was no statistically signi cant difference between the two groups in terms of maternal all-cause mortality, neonatal sepsis or all-cause mortality. Two recent systematic reviews [19,20] showed that the addition of a single dose of azithromycin at the time of delivery was associated with a lower risk of maternal sepsis but was not associated with maternal mortality, neonatal mortality, neonatal sepsis or suspected neonatal sepsis. The ndings of our systematic review are consistent with those of Tita et al's [13] research and two previous systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may arise from the fact that azithromycin is not widely used in Africa [ 15 ]. Two recent systematic evaluations [ 22 , 23 ] have shown that the addition of a single dose of azithromycin at the time of delivery is associated with a reduced risk of maternal sepsis. One of them evaluated indicators related to the prophylactic oral administration of a single dose of azithromycin antenatally in women with planned vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%